2019
DOI: 10.3390/jcm9010114
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Alcohol Hangover and Physical Endurance Performance: Walking the Samaria Gorge

Abstract: Alcohol hangover is a potentially debilitating state. Several studies have demonstrated that it does not seem to impair strength or short-term endurance, but its effects on continuous exercise performance/long-term endurance have never been investigated. Therefore, the aim of the current study was to assess hiking performance of participants who walked the 15.8 km Samaria Gorge in Crete, Greece. Participants completed a survey in the morning before walking the Gorge, and in the afternoon after completion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…As a result, aggregate symptom scores may be greater than zero, even when no alcohol has been consumed. A recent study [19] compared hangover symptoms between subjects with and without a hangover and demonstrated that several symptoms are not unique to the hangover state but are also present without having a hangover or consuming alcohol. In this study, n = 299 subjects who were on holiday in Greece (mean (SD) age of 38.9 (11.0) years old) completed the AHS in the morning before walking the Samaria Gorge.…”
Section: Symptoms May Also Be Present Without a Hangover Or Alcohol Cmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, aggregate symptom scores may be greater than zero, even when no alcohol has been consumed. A recent study [19] compared hangover symptoms between subjects with and without a hangover and demonstrated that several symptoms are not unique to the hangover state but are also present without having a hangover or consuming alcohol. In this study, n = 299 subjects who were on holiday in Greece (mean (SD) age of 38.9 (11.0) years old) completed the AHS in the morning before walking the Samaria Gorge.…”
Section: Symptoms May Also Be Present Without a Hangover Or Alcohol Cmentioning
confidence: 99%
“…Note: In contrast to the original AHS, scores range from 0 (absent) to 10 (extreme). Data from reference[19].…”
mentioning
confidence: 99%
“…3 : subject consumed white wine (Chardonnay), red wine (Pinot Noir), and tequila on a usual drinking occasion. 4 : subject consumed Scotch whiskey, beer, and red wine on a usual drinking occasion. 5 : this amount of alcohol units was also consumed on each test day.…”
Section: Resultsmentioning
confidence: 99%
“…The alcohol hangover is defined as "the combination of negative mental and physical symptoms which can be experienced after a single episode of alcohol consumption, starting when blood alcohol concentration (BAC) approaches zero" [1,2]. Recent research suggests that there is no BAC threshold for producing hangover, but that hangovers may occur at all BAC levels, and are most likely elicited following consumption of more alcohol than usual on a drinking occasion [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Verster et al [4] found that non-student subjects (N = 176) who consumed a mean (SD) of 3.0 (1.8) alcoholic drinks (10 g ethanol each) reported considerable next-morning hangover severity, i.e., a mean (SD) overall hangover severity score of 4.6 (2.4) on a 0-10 scale. Despite this, their peak estimated BAC was 0.03%.…”
Section: Heavy Drinkingmentioning
confidence: 99%